1999
DOI: 10.1292/jvms.61.631
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Gamma-Aminobutyric Acid Immunoreactivity and Acetylcholinesterase Activity in Nerve Fibers of the Mouse Adrenal Gland.

Abstract: ABSTRACT.The present immunohistochemical and enzyme histochemical study showed gamma-aminobutyric acid (GABA) immunoreactivity and acetylcholinesterase (AChE) activity in the mouse adrenal gland. Weak GABA immunoreactivity was seen in clusters of chromaffin cells showing noradrenaline fluorescence. This finding suggests that both GABA and noradrenaline may be released from the granules of noradrenaline cells by adequate stimuli. GABA-immunoreactive varicose nerve fibers densely contacted adrenaline cells and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…For example, Kosaka et al (1988) reported the coexistence of GAD and choline acetyltransferase in some cell types of the retina, cerebral cortex, basal forebrain, and spinal cord. Iwasa et al (1999) showed that GABA immunoreactivity is colocalized with AChE in nerve fibers of the mouse adrenal gland, and N'Guyen and Grzywacz (2000) found GABA and GAD immunoreactivities in the cholinergic amacrine cells of the adult turtle retina.…”
Section: Cytochemical Subgroups Within Loc or Mocmentioning
confidence: 99%
“…For example, Kosaka et al (1988) reported the coexistence of GAD and choline acetyltransferase in some cell types of the retina, cerebral cortex, basal forebrain, and spinal cord. Iwasa et al (1999) showed that GABA immunoreactivity is colocalized with AChE in nerve fibers of the mouse adrenal gland, and N'Guyen and Grzywacz (2000) found GABA and GAD immunoreactivities in the cholinergic amacrine cells of the adult turtle retina.…”
Section: Cytochemical Subgroups Within Loc or Mocmentioning
confidence: 99%
“…Moreover, no AChE-positive cells were found in either the capsule or the cortex and AChE-positive nerve fibers were rarely found in the capsule. In parallel, Watanabe et al (1990) and Iwasa et al (1991) reported thick and thin bundles of AChE-positive nerve fibers that ran directly through the cortex into the medulla of the mouse adrenal gland. Moreover, groups of AChE-positive chromaffin cells and intramedullary ganglion cells were reported also in the rat (Tomlinson and Coupland, 1990;Dagerlind et al, 1994) and bovine (De Diego, 2010) adrenal medulla.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, groups of AChE-positive chromaffin cells and intramedullary ganglion cells were reported also in the rat (Tomlinson and Coupland, 1990;Dagerlind et al, 1994) and bovine (De Diego, 2010) adrenal medulla. The presence of AChE in the ganglionic cells and some chromaffin cells may be related to the hydrolysis of a large amount of ACh used in controlling the chromaffin secretory activity (Iwasa et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations